2003
DOI: 10.1063/1.1587259
|View full text |Cite
|
Sign up to set email alerts
|

Spatially direct and indirect transitions observed for Si/Ge quantum dots

Abstract: The optical properties of Ge quantum dots embedded in Si were investigated by means of photoluminescence, with temperature and excitation power density as variable parameters. Two different types of recombination processes related to the Ge quantum dots were observed. A transfer from the spatially indirect to the spatially direct recombination in the type-II band lineup was observed with increasing temperature. A blueshift of the spatially indirect Ge quantum-dot-emission energy with increasing excitation powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 9 publications
3
24
0
Order By: Relevance
“…Exciting with a laser power of 10 mW, there is a gradual transition from a predominant low energy band to a dominating high energy band with increasing temperature. The temperature dependence consequently supports the interpretation given above where the low emission band is ascribed to the spatially indirect recombination and the high energy band is attributed to the spatially direct transitions ͑also discussed in our previous work 23 ͒. Raising the sample temperature in- creases the probability for the electrons to populate the higher energy level inside the Ge dot, which opens the possibility for the spatially direct transition.…”
Section: Temperature and Excitation Power Dependence Of Plsupporting
confidence: 71%
“…Exciting with a laser power of 10 mW, there is a gradual transition from a predominant low energy band to a dominating high energy band with increasing temperature. The temperature dependence consequently supports the interpretation given above where the low emission band is ascribed to the spatially indirect recombination and the high energy band is attributed to the spatially direct transitions ͑also discussed in our previous work 23 ͒. Raising the sample temperature in- creases the probability for the electrons to populate the higher energy level inside the Ge dot, which opens the possibility for the spatially direct transition.…”
Section: Temperature and Excitation Power Dependence Of Plsupporting
confidence: 71%
“…Although Ge is also a semiconductor with indirect band gap, one of the promising approaches to increase the luminescence efficiency is to use Ge/Si nanostructures like quantum wells and Ge self-assembled quantum dots (QDs). In such QDs, the selection rules can be relaxed due to the three-dimensional carrier localization and therefore the emission efficiency can be enhanced [2]- [4]. Moreover, it is easy to grow high-quality Ge QDs directly on Si wafer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the optical analysis of any SAQDs is usually performed using embedded dots, since the surface states act as efficient non-radiative channels for uncapped dots. Previous studies using uncapped SAQDs have indeed observed weaker photoluminescence ͑PL͒ as compared to capped dots on systems such as InAs/GaAs, 6 InGaAs/GaAs, 7 Ge/Si, 8 and InP/InGaP. 9 In contrast, uncapped InP/GaAs SAQDs present an efficient PL emission that allows us to obtain structural and optical properties from the same sample, which is actually a very important advantage when investigating SAQD properties.…”
Section: Introductionmentioning
confidence: 99%